Dimensi meta learning dalam transformasi pendidikan kristiani di Indonesia - Ana Lestari Uriptiningsih; Yonathan Salmon Efrayim Ngesthi; Carolina Etnasari Anjaya (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2022)
In the current digital era, life's challenges are increasingly complex, so it needs to be balanced by quality human resources superior to the previous era. In the context of Christian education, this can be realized through transformation efforts to form students who have a strong faith so that they are skilled at dealing with life's problems, can develop themselves into the character of Christ, and have an increasing impact on others and the world. This study aims to describe the importance of transforming Christian education and the gaps in its current implementation. The research method used is descriptive qualitative with a literature study approach to synthesize relevant previous research results. The results of this study indicate that meta-learning is a new